Analisa Kegagalan Emisi SO2 Hasil Pembakaran Batubara Pada Flue Gas Desulfurization (FGD) di PLTU Tanjung Jati B Unit 3 & 4 - Rianto Wibowo; Amirul Haq Rohmatullah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Tanjung Jati B Unit 3 & 4 Steam Power Plant (PLTU) is a steam power plant that uses coal as fuel. Burning coal produces exhaust emissions containing sulfur dioxide (SO2) which is dangerous for the environment. To overcome this, PLTU Tanjung Jati B Units 3 & 4 uses Flue Gas Desulphurization (FGD) to reduce SO2 emissions. This research aims to analyze the factors that cause FGD failure in reducing SO2 emissions, formulate efforts to overcome FGD failure and improve its performance, and develop a method for evaluating the effectiveness of FGD in reducing SO2 emissions. The research method used is literature study, primary data collection through observation and interviews, and data analysis. The research results show that the factors that cause FGD to fail in reducing SO2 emissions are blockage of the spray pipe and header pipe, blockage of the tray, and a decrease in the performance of the booster fan and absorber recirculation pump. The method for evaluating the effectiveness of FGD in reducing SO2 emissions is by analyzing de-Sox efficiency, flue gas flowrate and temperature, pressure drop, and ARP discharge pressure. Keywords: PLTU, FGD, SO2 emissions, de-Sox efficiency, flue gas flow rate, pressure drop, ARP discharge pressure. The method for evaluating the effectiveness of FGD in reducing SO2 emissions is by analyzing de-Sox efficiency, flue gas flowrate and temperature, pressure drop, and ARP discharge pressure.